2009
DOI: 10.1099/vir.0.009050-0
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus proteins PB1 and NS1 are subject to functionally important phosphorylation by protein kinase C

Abstract: The virulence of influenza A viruses depends on the activity of the viral RNA polymerase complex and viral regulatory phosphoproteins. We identified that the protein kinase C (PKC) inhibitor Gö 6976 had a post-entry anti-influenza viral effect, by using a polymerase activity-based reporter assay. This inhibitory effect was observed for influenza virus-infected cells as well as for cells transiently transfected with constructs for the RNA polymerase complex. Importantly, the in vitro analysis of viral protein p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
21
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
2
21
2
Order By: Relevance
“…Both domains contribute to the formation of IAV-NS1 homodimers, a prerequisite for IAV-NS1 to interact with its RNA targets and maintain its function (15)(16)(17). Interestingly, phosphorylation of IAV-NS1 has been reported to be functionally important for some IAV strains, and T215 is identified to be one of the potential target sites (18)(19)(20). However, modulation of IAV-NS1's action by host innate immune response is still poorly understood.…”
mentioning
confidence: 99%
“…Both domains contribute to the formation of IAV-NS1 homodimers, a prerequisite for IAV-NS1 to interact with its RNA targets and maintain its function (15)(16)(17). Interestingly, phosphorylation of IAV-NS1 has been reported to be functionally important for some IAV strains, and T215 is identified to be one of the potential target sites (18)(19)(20). However, modulation of IAV-NS1's action by host innate immune response is still poorly understood.…”
mentioning
confidence: 99%
“…Knockdown experiments in human cells revealed that physiological levels of PPP6C are required for efficient virus growth and for transcription and replication of the viral genome, suggesting an important role for PP6 and for the regulation of phosphorylation in the influenza A virus life cycle. Indeed, previous studies have identified numerous sites of phosphorylation in the proteomes of influenza A and B viruses, with roles for phosphorylation being implicated in virus entry and exit, nuclear localization, and protein oligomerization (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49).…”
mentioning
confidence: 99%
“…Phosphorylation was the first posttransla-tional modification described to affect NS1 (25), and although early reports established that NS1 phosphorylation is important for efficient viral replication (26,27), a recent study provided strong evidence that, at least for the A/Udorn/72 virus strain, only one out of three identified phosphorylation events affects NS1's functions (28). Two additional posttranslational modifications affecting NS1 were almost simultaneously described, both belonging to the group of UBL proteins (proteins exhibiting a tertiary structure similar to that of ubiquitin).…”
mentioning
confidence: 99%